Binary search algorithm for natural number targets - Senad Orhani (Journal Basic Science and Technology, 2022)
Targeting the number thought in a list is a common problem in computer science and is commonly implemented with the search algorithm. Numerical math games are a big thing for all of us. One of the really challenging games is targeting the number thought by the opponent. Therefore, the purpose of our study is to find the desired number through the binary search algorithm. For this study, we developed a pseudocode in the Python programming language, which gives the desired result followed after several successful steps. Our study results show that the algorithm was very efficient in solving the problem of finding the intended natural.